Educational ideas to postpone the end of the world - Rodrigues , Fabiana de Cássia (2022)
This paper refers to the book by Ailton Krenak (2019), Ideas to postpone the end of the world. The work brings a present hope in the possibility of “postponement”. Extending time, postponing the end of the world, would allow us to envision the construction of social relations beyond capital. The educational ideas highlighted in this text have in common the principle of inserting educators and students in the reins of the pedagogical process, inquiring and defining their purposes, thus acting consciously on behalf of collective objectives. We think that only through a path in which we are genuinely builders of reality is there a possibility of postponing the end of the world. And so, fight so that, perhaps, this is just the end of the world ruled by capital and not the end of the human species.